Evaluation of panoramic radiographs taken from 1,056 Turkish children - KARGÜL, BETÜL; BEKİROĞLU, GÜLNAZ NURAL; ERÇALIK YALÇINKAYA, ŞEBNEM (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2015)
Objective: Panoramic radiographs (PRs) play an important role in the diagnosis and treatment planning of a wide range of dental and maxillofacial diseases and conditions. To examine and to determine the status of oral lesions, dental anomalies and pathologies in panoramic radiographs, which were taken at the department of pediatric dentistry, Dental School, Marmara University, Istanbul, Turkey. Materials and Methods: This retrospective study consists of 1,056 randomly selected PRs of children aged from 4 to 12 years old, conducted at the department of pediatric dentistry at Dental School, Marmara University, between 5th December 2011 and 17th January 2012. The following information was obtained from the patients' records and PRs: Gender, age, presence or absence of oral lesions, dental anomalies and pathologies such as mesiodentes, supernumerary teeth, odontoma, radicular cyst, impacted tooth, and fusion. Results: One thousand and fifty-six PRs from 520 girls and 536 boys were observed. The mean and standard deviation age of the patients was 8.43 +/- 2.17. Among 1,056 patients, 457 (43.28%) of them had oral lesions, discovered by the PRs. The age of these 457 patients was ranged from 4 to 12 years. There were 37 (3.50%) mesiodentes, 9 (0.85%) supernumerary teeth, 4 (0.38%) odontoma, 12 (1.14%) radicular cyst, 16 (1.52%) impacted tooth, and 20 (1.89%) fusion. Conclusions: Oral lesions with a rate of 43.28% could be detected relatively at early age, as presented in the present study. Early treatment of these lesions, dental anomalies, and pathologies could avoid maxillofacial deformity and other complications.
Keywords: Children; oral symptoms; panoramic radiograph; DENTAL ANOMALIES; SUPERNUMERARY TEETH; INCIDENTAL FINDINGS; PRIMARY DENTITION; HYPODONTIA; PATHOLOGY; JAWS